THE EFFECT OF KNOWLEDGE AND ATTITUDE ON THE PRACTICE OF USING MOBILE JKN APPLICATIONS IN PARTICIPANTS OF BPJS KESEHATAN JEMBER BRANCH OFFICE - Agung Tri Anjono; Diana, Sulis (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
The use of JKN mobile applications is increasing along with the development of information technology. This study aims to analyse the effect of participants' knowledge and attitudes on satisfaction in using the JKN mobile application at the Jember Branch Office. This study uses quantitative research methods using analytical observational methods with a cross sectional approach. Probaility Sampling with Simple Random Sampling Technique with a total sample of 134 respondents. Data collection was carried out by filling out questionnaires and interviews made by researchers and filled in by respondents. The collected data were processed using the statistical test ‘Chi-Square’ The results showed that most respondents had good knowledge about the JKN mobile application as many as 89 people (66.4%), most respondents had a negative attitude about the JKN mobile application as many as 82 people (61.2%), most respondents were satisfied in using the JKN mobile application as many as 71 people (53%). The results of the Chi-square analysis test show that the p-value of 0.012 means that there is an influence of knowledge on satisfaction in using the JKN mobile application, the p-value of 0.000 means that there is an influence of attitude on satisfaction in using the JKN mobile application. It is expected that BPJS Kesehatan officers are more continuous about socialising the menu or features on the JKN mobile application directly to BPJS Kesehatan participants, currently patients who come to BPJS Kesehatan health facilities some have not used mobile JKN, so it needs the role of officers in educating patients and families about the features in the JKN mobile application.